Portugal Before and After the “Great Recession”: A Resilient Democracy? - Pinto, Antonio Costa (2019)
“The (new) Portuguese government … faces a herculean task in the application of an economic programme to bring the country out of its alarming decline”. The sentence above could have been written in 2011, but it was published in 1978, and shows that what Southern European countries experienced in 2011–2012 is not new to Portuguese citizens. Since its inception, Portuguese democracy has had to deal with economic and financial crises and austerity measures, with the exception of the decade following European accession (Teixeira and Pinto 2012). Although the first decade after accession was one of slight growth and investment, Portugal’s economy has been performing poorly since the beginning of this century, when the euro entered circulation. This is so much so that the years between 2000 and 2010 have been named ‘the lost decade’ (Reis 2013). Then, in May 2011, Portugal signed its third bailout agreement with the International Monetary Fund (IMF) and the European Union (EU) and was forced to implement severe austerity measures again. For a democracy that was celebrating its 40th anniversary, the word ‘crisis’ was all too familiar. Portugal was forced to solve the crisis through “internal devaluation”. Before and after the bailout, both the centre left (2009–2011) and the centre right (2011–2015) governments introduced unpopular measures, including severe wage and pension cuts, higher taxes, and, a sizeable decrease in social rights. Social and economic situations such as these are likely to have serious consequences for incumbent parties and therefore considerable party system changes were to be expected (Kriesi 2012). Yet, such has not been the case in Portugal, where, apart from some levels of fragmentation, little has changed (Lobo et al. 2011). This book explores the factors that might explain why some of the changes occurring in other Southern European democracies as an impact of the crisis have not been felt in Portugal. The chapter is organised as follows: in the next section, we introduce the impact of the 2008 financial crises in Portugal. We then move to the framework of the book and the main research questions. Finally, the main consequences of the crisis for Portuguese democracy will be explored, based on the chapters of the book.